The Creation of Man in Tafsir Al-Jawahir by Thanthawi Jawhar - Alya Muhibah; Heru Apriliaji; Mochammad Luthfie; Muhammad Haikal Pasha; M. Sugino Ramdhan; M. Ja’far Shodiq; Say Futriana; Widya Rosi Juliyanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research examines the concept of human creation according to Tafsir Al-Jawahir by Tantawi Jawhari, a commentary that combines interpretation of the Al-Qur'an with a scientific approach. This tafsir highlights how the Qur'an explains the creation of humans through several stages, starting from the earth to becoming perfect creatures. The process of human creation includes the phases of germfah (semen), alaqah (a clot of blood), mudghah (a clot of flesh), bone formation, and the impregnation of the spirit that brings human life. Tantawi uses the